AN INVESTIGATION OF THE SURGICAL ANATOMY OF THE PEDIATRIC ILIOTIBIAL BAND. Issue 3 (31st March 2019) - Wilson, Philip L.; Ellis, Henry B.; Richmond, Connor G.; Sabatino, Meagan J.; Wyatt, Charles W.; Zynda, Aaron J.; Ganley, Theodore J.; Shea, Kevin
Background: Previous work on adult specimens have demonstrated some differential thickness of the iliotibial band (ITB) tissue in different areas. The purpose of this study was twofold: 1) to quantitatively and qualitatively describe the relevant surgical anatomy of the ITB, at the level of the knee, in pediatric cadaveric specimens in which either an iliotibial band tenodesis or extraphyseal reconstruction would be considered, and 2) to provide recommendations that allow the surgeon to obtain the ideal graft in terms of tissue width and location on the larger ITB structure. Methods: Pediatric cadaveric specimens (n=24) were dissected by a group of fellowship trained pediatric orthopaedic surgeons. Digital photography of each specimen was obtained prior to collecting quantitative data of the ITB and its three main divisions using digital calipers and a coordinated measurement device (Hexagon Romer Absolute V3 CMM). Measurements included thickness, surface area, length, and width of each branch; surface area and length of each insertion; and distance of insertion in relation to other pertinent anatomical landmarks. Specimens were grouped into four age groups (Group 1: 2 year olds, Group 2: 3 and 4 year olds, Group 3: 5-7 year olds, and Group 4: 9-11 year olds). The four age groups were compared utilizing ANOVA and nonparametric Kruskal-Wallis tests with post-hoc analysis using the Tukey method. In order to correlate measurements and age, a Spearman's correlation was used. Results: All specimens (mean age 4.7 years; range 2-11) contained a visible ITB with a direct primary arm to Gerdy's tubercle. Sixteen specimens (66.6%) had a visible trifurcation point, in which the aggregate of ITB fibers diverge into three distinct branches: a direct arm, the iliopatellar branch, and the iliotendinous branch (Figure 1). Fibers from the central third of the iliotibial band, as described as the primary site for harvest, do not terminate on Gerdy's tubercle, but diverge to the patella, patellar tendon and a portion of Gerdy's tubercle. The length from the trifurcation point to the insertion of the direct arm at Gerdy's tubercle increased with each age group (21.3 mm, 29.9 mm, 31.5 mm, and 41.8 mm, respectively) with a significant difference seen between Group 1 and 4 (p<0.01) and Group 2 and 4 (p=0.03), indicating migration of this point with longitudinal growth. The mean thicknesses of the direct arm (0.55 mm), the iliopatellar branch (0.74 mm), and iliotendinous branch (0.42 mm) were not statistically different between age groups. Length, width, and surface area were also not statistically different between age groups. Conclusion: The ITB is a consistent, well-defined structure in pediatric specimens. While some longitudinal changes in the ITB and its insertions were seen with increasing age, the thickness and width of the direct arm of the ITB, typically harvested for extra-physeal ACL reconstruction, does not appear to differ between age groups and does not represent the thickest distal branch of the ITB. The location of ITB harvest may influence the impact that the extra-articular "capsular tightening" has on joint mechanics, including altering the compression across the joint, and/or the impact on the Pivot-Shift/rational laxity of the knee undergoing ITB reconstructions. Further study of the graft location/harvest and its impact on knee biomechanics is warranted. Figure 1: Surface anatomy from laser scanner and digital photography demonstrating the 3 main branches of the iliotibial band: direct arm (yellow), the iliotendinous branch (green), and the iIiopatellar branch (pink). Gerdy's Tubercle and the Patella are noted.